Formulações e métodos de solução na análise não-linear de treliças espaciais - Codes, Rodrigo Amaral de (1978)
The main objective of this work is to examine the numerical performance of the Total Lagrangean and Updated Lagragean formulations for geometrically and materially nonlinear analysis of space trusses, and the most commonly used nonlinear equation solution algorithms. These formulations, and two others; are implemented in the ANALITE program. The Total Lagrangean and Updated Lagrangean formulations are developed based on general principles of continuum mechanics. They make possible the nonlinear analysis of large displacements and large deformations. The structure is discretizeted by the finite element method, using the displacement model. The solution of the nonlinear equation system can be carried out by several incremental procedures: Newton iteration type (Newton-Raphson and modified Newton-Raphson), conventional incremental, improved incremental, first-order self-correcting incremental, and some numerical integration techniques (fourth-order Runge-Kutta and Hamming's predictor-corrector). Several examples comparing the different possibilities of the program are presented and commented.